Comparative Evaluation of the Antibacterial Activity of Aqueous and Ethanolic Extracts of (Thymus vulgaris) Against Acinetobacter baumannii - Nibras Salman Faraj (Jurnal Biologi, 2025)
Acinetobacter baumannii is a Gram-negative, pathogenic bacterium associated with multidrug-resistant hospital infections, making it a prime target for research into alternative treatments the work aimed to study the antibacterial properties of alcoholic and aqueous extracts of thyme. One hundread blood samples were collected from patients admitted to the Intensive Care Unit (ICU) at Sharqat General Hospital for the period from 1/9/2024 to 30/3/2025. Patient information was recorded, including patient name, age, and type of infection related to the patient’s condition. Bacterial isolates were diagnosed based on phenotypic characteristics of bacteria, colony growth, and basic biochemical tests. The antibacterial activity of the alcoholic and aqueous extracts was evaluated by well diffusion method at concentrations of (5, 10, 25, 50, and 100) µg/ml. The results of testing the effectiveness of the alcoholic and aqueous extracts of thyme against Acinetobacter baumannii bacteria showed that the alcoholic extract recorded higher activity at all concentrations compared to the aqueous extract. At the lowest concentration (5 µg/mL), the diameter of the inhibition zone for the alcoholic extract was 4.5 ± 0.5 mm, while it was 3.2 ± 0.4 mm for the aqueous extract. When the concentration was increased to 10 µg/mL, the activity increased to 7.2 ± 0.7 mm for the alcoholic extract versus 6.3 ± 0.6 mm for the aqueous extract. At a concentration of 25 µg/mL, the inhibition zone reached 10.2 ± 0.6 mm for the alcoholic extract and 9.8 ± 0.7 mm for the aqueous extract, which are slight differences but continue to favor the alcoholic extract. At a concentration of 50 µg/mL, the values were 15.2 ± 0.7 mm for the alcoholic extract and 13.5 ± 0.8 mm for the aqueous extract. Finally, at the highest tested concentration of 100 µg/mL, inhibition reached its maximum levels, recording 19.3 ± 0.8 mm for the alcoholic extract and 17.2 ± 0.9 mm for the aqueous extract The alcoholic extract showed higher inhibitory activity than the aqueous extract against A. baumannii at all tested concentrations.